Realistic and Symbolic Threats: The Social Basis of Mass-Migration Related Fear in Contemporary Hungary (Szociológiai Szemle, 2023)
This paper describes the different components of mass-migration-related fear based on the theoretical framework of integrated threat theory developed by Stephan et al. (1999) and reveals the social basis of fear in relation to the recent migration crisis that has been affecting Europe since 2015. The paper uses survey data from the research entitled The Social Aspects of the 2015 Migration Crisis in Hungary implemented in 2016 by TÁRKI Social Research Institute. Results show that the majority of respondents worried a lot about both the realistic and the symbolic threat of migration (around 60% of respondents perceive intense migration related threats). We identified only a small subsample of people who worried more about the realistic than the symbolic threat of mass migration (15% of respondents), and only a tiny subsample of respondents who worried more about the symbolic than realistic the threat of mass migration. Regarding the socio-demographic predictors, respondents’ age as well as their place of residence played important roles in the perception of threat, but not exactly in the same way as in case of xenophobic attitudes. On the other hand, respondents’ level of educational and political activity did not predict perceptions of threat, in contrast to our hypothesis based on the literature about predictors of xenophobia. In addition, personal contact with migrants, social trust, political activity and affiliation are also directly associated with the perceived threat towards mass migration, both in the European and the national context.